Pengembangan Aplikasi Monitoring dan Pengelolaan E-Commerce Admin Isitaman berbasis Web menggunakan Framework Laravel (Studi Kasus: PT Java Indo Arjuna) - Naufal Widhi Ashshiddiqi; Widhy Hayuhardhika Nugraha Putra; Welly Purnomo (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2022)
E-Commerce is the process of buying and selling goods to consumers that can be done more quickly and efficiently, and is not limited by space and time. Supported by the covid-19 pandemic, online transactions or e-commerce increased rapidly compared to the previous year, which had an impact on PT. Java Indo Arjuna, a company engaged in plant cultivation, conducts sales manually, from product management to transactions, so a platform is needed that can handle these management problems. This is the background for the development of an e-commerce admin monitoring and management system called isitaman with the agile scrum model method because the system requirements are not known for sure. From the Agile Scrum method, 13 use cases are generated as basic needs, 8 main features, 4 main admin features, 17 product backlogs, and 20 sprint backlogs. From the 20 sprint backlogs, 4 sprint iterations were produced that implemented sequence diagrams, activity diagrams, user interfaces, APIs, source code, black box testing and sprint reviews as well as retrospectives. From blackbox testing, the results are 100% valid.